Teknik Mendongeng bagi Guru dan Orangtua untuk Anak Usia Dini - indrawati, dwi; Farantika, Dessy; Shofwan, arif muzayin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2023)
There are many storytelling techniques that experts offer. A teacher and parents are expected to master storytelling techniques for early childhood. This qualitative descriptive research with a literature study explains storytelling techniques for teachers and parents in early childhood. The data analysis technique uses content analysis by sorting out data according to the objectives and research problems. This paper produces several things as follows. First, storytelling tips for early childhood that teachers and parents should know, including appropriate and interesting fairy tale references, telling interesting and clear fairy tales, expression in storytelling according to the storyline, choosing fairy tales that are appropriate for the child's age, and determine the duration of sufficient time in storytelling. Second, several techniques that must be mastered by teachers and parents in storytelling for early childhood, include interpretation techniques, namely finding the intent, purpose, meaning, meaning and like from a script or story text; representation techniques, namely how to convey a script or story text by using the body as a tool; and creativity techniques, namely creativity that supports a fairy tale performance, not creativity that weakens. Third, the technique offered to teachers and parents for storytelling in early childhood in this study is the CAS CIS CUS technique. CAS is held at the beginning of the story's opening. CIS is a core part of storytelling that contains stories and moral messages. CUS is the closing part of the storytelling activity which aims to invite listeners to follow a good moral message.